Jejunum Perforation Caused by Malignant Lymphoma Following Methotrexate Therapy for Rheumatoid Arthritis - Oe, Shoshiro; Yamaoka, Ryoya; Furumoto, Katsuyoshi; Yamaguchi, Masahiko (Nippon Shokaki Geka Gakkai zasshi, 2020)
A 62-year-old man was given a diagnosis of chronic rheumatoid arthritis and treated with methotrexate for 5 years. He came to our hospital complaining of acute abdominal pain after having dinner. He presented with abdominal tenderness and muscular defense in the left upper abdomen. CT revealed intraperitoneal free air, and emergency operation was performed under the diagnosis of acute peritonitis due to gastro-intestinal perforation. During the operation we found an 8-mm perforation in the jejunum, located approximately 120 cm distant from the ligament of Treitz and therefore performed partial resection of the jejunum. The specimen showed an ulcer surrounded with embankment, and histological examination revealed large atypical lymphocytes, positive for CD20, and EBV-encoded small RNA in situ hybridization. We concluded that it was malignant lymphoma, diffuse large B cell type. Lymphoma occurs in some cases in which methotrexate is used for treatment, and it is classified with methotrexate-associated lymphoproliferative disorder. To the best of our knowledge, 7 cases, including this patient with perforation of small intestine caused by methotrexate-associated lymphoproliferative disorder, have been reported in Japan.